Pengembangan Alat Spin Ball Untuk Batting Softball - Hakim Mohammad (YLPK Mahardhika, 2022)
The purpose of this research is that in practicing softball games the hitting technique is more efficient and effective because it does not go back and forth to take the ball when it has been hit by an athlete during practice. This study uses research and development methods. The research sample uses two validations, namely the validation of material experts and media experts, and uses two variables, namely small scale and large scale. Material experts get a percentage of the spin ball tool for softball batting of 87.5% that the spin ball tool is feasible to use. While media experts get a percentage of 81.2% which means it is said to be suitable for use. Small-scale respondents amounted to 7 people with a percentage of 72.8. This large-scale study involved 15 respondents from 3 universities in Semarang city with a percentage of 77.3%. The study concludes that the 4 variables categorize the spin ball tool for softball batting as feasible to use